Properti Psikometri dan Analisis Campuran Model Rasch dari Body Regulation Exercise Questionnaire (BREQ-3) - Andika, Bryan; Tunggawan, Ingrid; Yudiarso, Ananta (Universitas Airlangga, 2025)
This study aimed to test the reliability and validity of the Indonesian-translated Body Regulation Exercise Questionnaire (BREQ-3), originally developed by Wilson et al. (2006), using Rasch analysis. A total of 408 Indonesian participants aged 18–25 years completed the survey. The results supported the unidimensionality of each BREQ-3 subscale. The 5-point Likert scale functioned adequately, except for the amotivation subscale. Both person and item reliability, as well as separation indices, were within acceptable ranges. Most items effectively measured exercise regulation, although six items were identified requiring revision. Three items, from the External and Intrinsic Regulation subscales, showed gender bias. Further analysis using the Mixture Rasch Model indicated that the identified classes were not distinguished by gender or age. Overall, the findings support the use of the Indonesian version of the BREQ-3 for assessing physical activity regulation in young adults and suggest directions for future research.